(untitled) ("Journal "U". Economy. Management. Finance.", 2022)
The modern transformation of the world order is taking place as part of the fourth wave of digitalization, which is changing the very attitude towards supply chains. The object of this study will be the study of digital technologies used in practice in the EAEU. The practical significance of this scientific work lies in the opportunity to study both the current state of affairs in the industry and possible ways of inheriting the use of new digital products within a given economic space in the future. The result of this study was the study of the used dynamic indexes for the distribution of flexible data libraries, as well as the use of synchronous distribution of big-data within a single system of rapid streaming response.